Effect of anti-oxidants and oxidative stress parameters on ram semen after the freeze-thawing process - Bucak, Mustafa Numan; Atessahin, Ahmet; Yuce, Abdurrauf (Elsevier Science Bv, 2008)
Oxidative damage to sperm resulting from reactive oxygen species generated by the cellular components of semen is one of the main causes for the decline in motility and fertility of sperm during the freeze-thawing process. The aim of this study was thus to determine the effects of anti-oxidants on standard semen parameters, lipid peroxidation (LPO) and anti-oxidant activities after the freeze-thawing of ram semen. Ejaculates collected from four Akkaraman rains, were pooled and evaluated at 33 OC. Semen samples were diluted in a Tris-based extender containing the anti-oxidants glutathione (GSH) (5 mM), oxidized glutathione (GSSG) (5 mM) or cysteine (5 mM) and an extender containing no anti-oxidants (control), cooled to 5 degrees C and frozen in 0.25 ml French straws. Frozen straws were thawed individually for 20 s in a water bath (37 degrees C) for microscopic evaluation. The use of an extender supplemented with cysteine led to the highest (P < 0.01) post-thaw motility (61.0 +/- 1.9%), compared to the other treatment groups. No significant differences were observed in viability, acrosome damage and total abnormalities, and following the hypo-osmotic swelling test (HOST), following supplementation with anti-oxidants after the thawing of the semen. Following the thawing process, the levels of malondialdehyde (MDA) did not change with the addition of anti-oxidants, compared to the control. The GSH level and glutathione peroxidase (GSH-PX) activity remained significantly higher upon the addition of GSH (3.33 +/- 0.14 nmol/ml and 22.02 +/- 11.27 IU/g protein) and GSSG (3.24 +/- 0.08 nmol/ml and 20.17 +/- 3.38 IU/g protein) compared to the other treatment (P < 0.001) groups. Only cysteine significantly elevated the activity of catalase (CAT, 842.40 +/- 90.42 kU/l) following the freeze-thawing process. The Vitamin E (VitE) level was significantly higher, when compared to GSSG, cysteine and the control, when GSH (4.21 +/- 0.20 mg/dl) was added to the freezing extender (P < 0.001). It could be concluded that future efforts aimed on improving the efficiency of cryopreservation of ram sperm should concentrate on the use of anti-oxidant additives. The results obtained provide a new approach to the cryopreservation of rain semen, and could positively contribute to intensive sheep production. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: anti-oxidants; anti-oxidant activities; freezing; ram semen; semen parameters